2020
DOI: 10.1371/journal.pone.0234410
|View full text |Cite
|
Sign up to set email alerts
|

An invasive plant experiences greater benefits of root morphology from enhancing nutrient competition associated with arbuscular mycorrhizae in karst soil than a native plant

Abstract: The Eupatorium adenophorum have widespread invaded the karst ecosystem of southwest China and threatened the regional native community stability. Arbuscular mycorrhizae (AM) plays an important role in promoting growth for host plants via root external mycelia. However, whether AM regulates plant root traits underlying competition between invasive and native species via mycorrhizal networks in karst habitats, remains unclear. An experiment was conducted in a microcosm composed of two planting compartments flank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 56 publications
4
19
0
1
Order By: Relevance
“…AM fungi can induce the expression of mycorrhiza-specific phosphate (Pi) transporters, such as StPT3 in potato and ZEAma and Pht1 and Pht6 in maize ( Javot et al, 2007 ), respectively. In addition, AM fungi can regulate root architecture ( Xia et al, 2020 ) and produce extensive mycelium for exploring rhizosphere scale ( Shen et al, 2020 ) to help plants absorb nutrients, which are the essential mechanisms for plants to adapt to some special habitat, such as karst habitat with nutrient deficiency owning to thin and barren soil layer ( Li et al, 2002 ). Conversely, the host plant provides sugars and lipids to the fungal partner, such as AM fungi ( Jiang et al, 2017 ; Rich et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…AM fungi can induce the expression of mycorrhiza-specific phosphate (Pi) transporters, such as StPT3 in potato and ZEAma and Pht1 and Pht6 in maize ( Javot et al, 2007 ), respectively. In addition, AM fungi can regulate root architecture ( Xia et al, 2020 ) and produce extensive mycelium for exploring rhizosphere scale ( Shen et al, 2020 ) to help plants absorb nutrients, which are the essential mechanisms for plants to adapt to some special habitat, such as karst habitat with nutrient deficiency owning to thin and barren soil layer ( Li et al, 2002 ). Conversely, the host plant provides sugars and lipids to the fungal partner, such as AM fungi ( Jiang et al, 2017 ; Rich et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was consistent with H1. The positive effects of AM colonization on plant growth performance and nutrient uptakes have been well reported, particularly in nutrient‐poor heterogeneous soils, as AM hyphae can help the root systems expand plants' absorption area to access soil resources (He et al, 2017; Xia, Wang, et al, 2020). For example, AM fungi promoted biomass production and N and P accumulations of pioneer herbs in nutrient‐deficient karst areas (He et al, 2017, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive AM fungal root epitaxial hyphae are an important pathway for plants to obtain nutrients from soil patches compared with root foraging because the carbon cost of finer hyphae growth is often less than thicker root growth (Chen et al, 2018; Smith & David Read, 2008). Numerous studies have widely recognized AM fungi's positive role in promoting host plants' growth and nutrient acquisition, particularly in heterogeneous soil patches (Croft et al, 2012; Smith & David Read, 2008; Xia, Wang, et al, 2020). Specifically, AM fungal hyphae detect and respond to nutrient patches outside the rhizosphere in heterogeneous soils for additional resources (Shi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…AM fungi formed a symbiotic relationship with 80% of terrestrial plants [ 18 , 19 ], improve plant growth, nutrient accumulation [ 20 , 21 ], enhance drought stress tolerance [ 22 ] and maintain soil structure [ 23 ], e.g. Guo et al (2021) [ 24 ] proposed that AM fungi differently affected the competitive ability of Broussonetia papyrifera and Carpinus pubescens ; Xia et al (2020) [ 25 ] also showed that AM fungi increased nutrients of host plants by regulating the morphological development of karst plant roots. In addition, Shi et al (2015) [ 26 ] illustrated that AM fungi increased the biomass, N, and P content in shoots and roots of plants.…”
Section: Introductionmentioning
confidence: 99%